IT Asset Assessment Using Quantitative Risk Analysis (QRA) Method at XYZ Cafe - Rahmat Yasirandi; Emiya Fefayosa Br Tarigan (Indonesia Journal on Computing (Indo-JC), 2021)
Many companies are starting to invest in information technology (IT) assets to improve their business performance and services in this era. This includes modern cafes, which are becoming a promising business trend, especially if they have branches in various places. As with XYZ Cafe, IT Assets play an essential role in running the business. This research has succeeded in utilizing the Quantitative Risk Analysis (QRA) Method to perform calculations and tabulations for any potential risks. The results show the increase in the value of losses by 371.5% of the issued IT Asset investment capital, or 477,388,063 Rupiah. In detail, through Across Asset Analysis, Across Asset Value is at the top of the rank, namely Mini PC, with a loss value of 127,440,000 Rupiah. Through Across Risk Analysis, the Accidental Errors is in the first rank with a loss value of 184,038,000 Rupiah. This result implies that stakeholders can develop and plan mitigation actions to reduce potential losses for the company. Mitigation actions can be in the form of regulations, standard operating procedures (SOP), proposed monitoring applications, or strategic plan at top-level management so every threat and risk can be controlled and managed.